Study of natural course of serous macular detachment in pregnancy induced hypertensive patients at a tertiary care centre - Devegowda, Shilpa Yellur; Nagaraj, Kalpana Badami; Rajanna, Hithashree Hampannavar; Chikhanumanthappa, Hemalatha B; Bypareddy, Ravi; N, Manoj Kumar; Tumbadi, Kavitha L; Basumatary, Jessica (Nepalese Journal of Ophthalmology, 2022)
Introduction: The research aimed to study the natural course of serous macular detachment SRD) in patients with pregnancy induced hypertension (PIH), and document fundus changes, OCT findings and visual outcome. Materials and methods: This is a prospective observational study. Admitted patients underwent ocular screening, and detailed dilated indirect ophthalmoscopy. Those with serous macular detachment were further evaluated with OCT; characteristics of OCT analysed and recorded. All eyes were followed up till macular resolution was noted. Results: Out of 4950 cases, 22 patients (38 eyes) had serous macular detachment. Mean central macular thickness (CMT) was 512.29 (SD 242.074). RPE irregularity (31.6%),subretinal hyperreflective dots (26.3%) and subretinal membranes (23.7%) were more commonly seen OCT features in these eyes. The difference between mean vision and mean central macular thickness at different intervals was statistically significant : F(3, 111)=65.514, p - 0.001; F(3, 111)=47.331, p – 0.001 respectively. All eyes had resolution of retinal detachment with full visual recovery following delivery. However, 10 pregnancies had foetal mortality. Conclusion: The incidence of ocular affection in pregnancy induced hypertension is 1-2%. Retinal detachment in such cases have good visual potential following termination of pregnancy. However, the cases had a high incidence of foetal demise. Therefore, early emphasis on early detection of ocular involvement in pregnancy induced hypertension and timely intervention is focused on to prevent foetal demise.